The Scheme of interlaced scuta in the roman mosaic and the case of Desenzano (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2011)
The orthogonal pattern of tangent crosses of interlaced scuta occurs in many roman mosaic pavements, from the II century B.C. to the VIII century A.D., in some regions of the Roman Empire (Achaia, Africa Proconsularis, Arabia, Aquitania, Belgica, Cyprus, Hispania, Italia, Mauretania Caesariensis, Numidia, Palaestina, Sardinia, Syria). The first part of the article is about the scheme in general and the diffusion of its variants. The second part focuses on the mosaic pavement of the entrance of the roman villa in Desenzano del Garda, on the features of the scheme, on the filling elements of the decoration (for instance “the knot”) and on the function of the vestibule, strictly linked to the pavement and to the monumental compound of the villa.
Keywords: Desenzano del Garda; late antique; mosaic; roman; roman villa; shield; scuta; vestibule